211. STUDENT (CROWD SOURCED) ASSESSMENT OF LAPAROSCOPIC ASSISTED PERCUTANEOUS NEEDLE JEJUNOSTOMY PLACEMENT IS EQUIVALENT TO EXPERT ASSESSMENT, EXCEPT FOR PROCEDURE-SPECIFIC STEPS. (24th September 2022) - Van Veer, Hans; Van der Biest, Femke; Corcoles, Laurence; Van den Bergh, Gert; Nafteux, Philippe; Depypere, Lieven
Abstract: Objective and Structured Assessment of Technical Skills (OSATS) is an important and frequently used method to give feedback on surgical skills during surgical training. Feedback is usually given by qualified surgeons, but their availability is often limited. Aim of our study was to investigate whether OSATS performed by novice medical students and students trained in a laparoscopic jejunostomy simulation setup was equivalent to OSATS performed by experts in laparoscopic assisted percutaneous needle jejunostomy placement. Fifty-six volunteers (32 inexperienced students, 12 trained students and 12 expert surgeons) were invited to participate. An instruction video with the procedure's essential steps was displayed on an online survey platform. Thereafter five edited videos with essential steps of the procedure, performed by operators with a different level of expertise, were shown. Each video was followed by a standardized OSATS form, assessing nine different procedural aspects: fluency of the entire procedure, use of instruments, tissue respect, placement of stitches, tissue bridge between bowel and wall, submucosal needle tunneling, advancing the catheter, camera use and end result. Nonparametric statistics were used. Thirty-seven (66%) volunteers—21 novice students (66%), 8 trained students (67%) and 8 surgeons (67%)—completed all five forms within 30 days. Median time to complete OSATS forms for novice students, trained students and experts was 22, 21 and 14.5 days respectively (p = 0.88). Median time needed per video was 825, 881 and 793 seconds respectively (p = 0.60). Average total scores per item showed no differences between novice students, trained and experts, except for items submucosal needle tunneling" (p = 0.0082) and advancing the catheter" (p = 0.0154) which both were rated higher by experts than by both groups of students. Using standardized OSATS to evaluate laparoscopic assisted percutaneous needle jejunostomy placement, steps with common laparoscopic skills were rated equally by novice students, trained students and experts. These skills can be correctly evaluated without advanced training of the evaluator. Two procedure-specific items were rated differently by experts, compared to students. These procedure-specific items probably need more advanced training, explaining the different appreciation of the assessed manipulations by expert surgeons.